2016
DOI: 10.1016/j.vaccine.2016.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pertussis and influenza immunization coverage and attitude of health care workers towards these recommendations in Flanders, Belgium

Abstract: In Belgium, pertussis vaccination is recommended for all pregnant women in every pregnancy. Adults in close contact with young infants are equally advised to receive a pertussis containing booster dose. Maternal influenza vaccination is likewise recommended in Belgium in the second or third trimester of pregnancy, within the influenza season. A quantitative multicenter survey study has been performed between October 2014 and May 2015 in both postpartum women (N=823, response rate=89.2%) and health care workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 19 publications
7
51
1
1
Order By: Relevance
“…To mitigate this problem, a possible solution consists in the provision of auditable educational training to HCPs contributing to ANC services such as GPs, gynecologists and midwives, to improve their confidence and inclination to discuss vaccination with expectant mothers. A second critical issue, emphasized by many respondents, is the reported skeptical attitude toward vaccinations among midwives and gynecologists in their district: this is consistent with findings in the literature (27,28). For this reason, in order to understand why HCPs have this attitude, university courses designed for midwives and gynecologists should be revised.…”
Section: Discussionsupporting
confidence: 62%
“…To mitigate this problem, a possible solution consists in the provision of auditable educational training to HCPs contributing to ANC services such as GPs, gynecologists and midwives, to improve their confidence and inclination to discuss vaccination with expectant mothers. A second critical issue, emphasized by many respondents, is the reported skeptical attitude toward vaccinations among midwives and gynecologists in their district: this is consistent with findings in the literature (27,28). For this reason, in order to understand why HCPs have this attitude, university courses designed for midwives and gynecologists should be revised.…”
Section: Discussionsupporting
confidence: 62%
“…For example, less than half of midwives in Ontario reported having sufficient knowledge of immunisation (Lee, Saskin et al 2005). A recent survey of health providers in Belgium found one-quarter of midwives recommended influenza and pertussis vaccines to their pregnant patients (Maertens, Braeckman et al 2016), and a similar study from Canada suggested midwives take a less active role in promoting immunisation compared to other healthcare providers (Dube, Vivion et al 2013). This study aimed to assess the knowledge, attitudes and learning needs of midwives in hospital X, the only public tertiary maternity hospital in the Australian state of XX.…”
Section: Introductionmentioning
confidence: 99%
“…but still falls short of national target rates aiming for universal coverage of >90%. In uenza coverage, on the other hand, is far from satisfactory even when compared to coverage in other countries like the United States (49.1% 13 ) or Belgium (45% 18 ).…”
Section: Resultsmentioning
confidence: 90%